URBAN POPULATION AND INCOME INEQUALITY IN INDONESIA: PANEL DATA ANALYSIS 2011–2024 - Miladiah, Rena; Rahmayani, Dwi (Jurnal REP (Riset Ekonomi Pembangunan), 2025)
This study aims to analyze the effect of gross regional domestic product per capita, proportion of urban population, labor force participation rate, and inflation on income inequality among provinces in Indonesia. The method used is panel data regression with a fixed effect model approach, using data from 33 provinces from 2011 to 2024. The results show that the proportion of urban population hurts income inequality, which suggests that an increase in the number of people living in urban areas can contribute to reducing income inequality. The labor force participation rate shows a positive but insignificant effect. Meanwhile, inflation has a positive effect, reflecting that price pressures widen inequality. Gross regional domestic product per capita has a positive effect, while the square of gross regional domestic product per capita has a negative effect. These findings are consistent with Kuznet's hypothesis, which describes a nonlinear relationship pattern between growth and inequality, and support the Phillips curve, which ex-plains that rising inflation can worsen income distribution.